Concepción pedagógica de la formación permanente del docente universitario en didáctica de la educación superior en Ecuador - Díaz Ocampo, Eduardo; Venet Muñoz, Regina; Álvarez Cortés, Alexis Benancio; Guerra González, Calixto (Universidad de Costa Rica, 2018)
This article presents the results obtained from a doctoral thesis developed at the State Technical University of Quevedo, Ecuador, from September 2014 to December 2017; the inadequate updating and systematization in Teaching of Higher Education of teachers is addressed, as content to be treated in permanent professional training. Its objective is: to elaborate a pedagogical conception of the permanent formation of the university teacher in Didactics of Higher Education. The methodological approach used was mixed, the information was collected using the written survey techniques; as instruments: structured questionnaire applied to experts, methods of analysis and synthesis; the modeling and the systemic-structural-functional, were applied in the construction of the scientific contributions; consultation with users, through socialization workshops (23 university teachers) and expert criteria, through the Delphi method (30 experts), in assessing the relevance of the results presented; the statistical processing was carried out with the SPSS v 16. The results show the feasibility and relevance of the scientific contributions, demonstrating that its practical application achieved positive transformations in the professional performance of university professors, which indicates its applicability and scope, so they can be used as support for the improvement of the permanent professional training of the university teacher.